ANALISIS PERFORMA KOLEKTOR SURYA PELAT DATAR DENGAN SIRIP MELINTANG BERONGGA DISUSUN ALIGNED - Alhafidz, Ahmad Husein; Astawa, Ketut; Sucipta, Made (Teknik Desain Mekanika, 2024)
Abstract The solar collector is a decent technology developed in Indonesia because Indonesia is in the global-speaking groundwork in the utilization and development of solar energy. This research uses experimental methods to observe hot transplaces that occur in the solar collector. The solar collector studied earning extra hollow fins that were in the solar collector and the fins were given a long-term hole and washed aligned transverse from the direction of the fluid flow. To increase the solar collector's performance is given a variation in the flow rate of mass ?1, ?2, and ?3 of 0,0009; 0,0019; and 0,0023 kg/s at 32 ?C. The results showed that in the solar collector there was a temperature of the highest temperature and energy use in the variation of ?3 of 0.0023 kg/s with useful energy of 102,81 w and the highest efficiency in variation ?2 of 0.0019 kg/s in number 26,55%. But the average useful energy and highest average efficiency is in variation ?3 of 0,0023 kg/s in 77,15 W and 19,78%. This shows that variation ? has an effect on improving solar collector performance. Keywords: Transverse hollow finns, Square-shaped holes, Aligned, Usable energy, Efficiency